1997
DOI: 10.1111/j.1525-1470.1997.tb00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Occurrence of Lichen Striatusin Siblings

Abstract: Lichen striatus (LS) is a self-limiting linear papular dermatosis of unknown etiology seen mostly in children. We report LS occurring in two pairs of siblings: two sisters who had LS at an interval of 6 months and a brother and sister who had the dermatosis contemporaneously after an episode of flulike fever. In all four patients family history was positive for atopy. LS is frequently associated with atopic diseases. The abnormal immune status of patients with atopy may be a predisposing factor in the inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 8 publications
1
21
0
1
Order By: Relevance
“…Although several studies have suggested that an infective agent could be the triggering factor in lichen striatus (6,10,21,25–27), the number of patients with symptoms of a prodromic or associated infection was too low in our series to confirm this theory. However, the possibility cannot be ruled out that the infection triggering lichen striatus may remain totally asymptomatic in the majority of affected children.…”
Section: Discussionmentioning
confidence: 55%
“…Although several studies have suggested that an infective agent could be the triggering factor in lichen striatus (6,10,21,25–27), the number of patients with symptoms of a prodromic or associated infection was too low in our series to confirm this theory. However, the possibility cannot be ruled out that the infection triggering lichen striatus may remain totally asymptomatic in the majority of affected children.…”
Section: Discussionmentioning
confidence: 55%
“…78 Some speculate that LStr occurs because of the interaction of a number of specific sporadic events: atopy; viral infection at a certain age; and genetic predisposition. 79 …”
Section: Pathogenesismentioning
confidence: 97%
“…In the discussions regarding the pathogenesis of AB or adult LS, it is of interest that in these reports the cited articles always concern LS. The main hypothesis is that, beside genetic factors [29], acquired stimuli, like a viral infection [3]or a trauma, induce loss of immunotolerance resulting in a T-cell-mediated inflammatory reaction against keratinocytes, which themselves show genetic mosaicism and are arranged along the lines of Blaschko [11, 14, 16, 17, 18]. Also the hypothesis of a somatic mutation of a keratinocytic clone, which could induce an autoimmune response of the host [27], similar to the graft-versus-host reaction, is cited [15, 17, 18].…”
Section: Discussionmentioning
confidence: 99%